2016
DOI: 10.1016/j.adengl.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Pseudolymphomas

Abstract: The term cutaneous pseudolymphoma refers to benign reactive lymphoid proliferations in the skin that simulate cutaneous lymphomas. It is a purely descriptive term that encompasses various reactive conditions with a varied etiology, pathogenesis, clinical presentation, histology, and behavior. We present a review of the different types of cutaneous pseudolymphoma. To reach a correct diagnosis, it is necessary to contrast clinical, histologic, immunophenotypic, and molecular findings. Even with these data, in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 114 publications
0
27
0
1
Order By: Relevance
“…Treatment consists mainly of the avoidance of causative allergens. The allergens implicated include phosphorus, N‐isopropyl‐N‐phenyl‐4‐phenylenediamine, ethylenediamine, dihydrochloride, cobalt naphthenate, nickel sulfate, paraphenylenediamine, gold sodium thiosulfate, zinc, squaric acid dibutylester, and methylchloroisothiazolinone (Romero‐Perez, Blanes, & Encabo‐Duran, ). Treatments include local and intralesional corticosteroids and tacrolimus ointments.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment consists mainly of the avoidance of causative allergens. The allergens implicated include phosphorus, N‐isopropyl‐N‐phenyl‐4‐phenylenediamine, ethylenediamine, dihydrochloride, cobalt naphthenate, nickel sulfate, paraphenylenediamine, gold sodium thiosulfate, zinc, squaric acid dibutylester, and methylchloroisothiazolinone (Romero‐Perez, Blanes, & Encabo‐Duran, ). Treatments include local and intralesional corticosteroids and tacrolimus ointments.…”
Section: Discussionmentioning
confidence: 99%
“…Magro et al suggested that antihistamines may be associated with atypical lymphoid hyperplasia in some patients (24,25). Other drugs that can be involved in cutaneous pseudolymphomatous reactions are angiotensin-converting enzyme (ACE) inhibitors, betablockers, calcium channel blockers, diuretics, cytotoxic agents (ciclosporin, methotrexate), rheumatology drugs (gold, salicylates, phenacetin, D-penicillamine, allopurinol, non-steroidal anti-inflammatory drugs (NSAIDs)), antibiotics, benzodiazepines, procainamide, oestrogens, progesterone and lovastatin (26). In a recent paper by Safa et al (27), a female patient developed erythrodermic CD8 + pseudolymphoma during infliximab treatment and was treated successfully with ciclosporin after cessation of infliximab therapy.…”
Section: Treatment According To Cutaneous Pseudolymphoma Aetiologymentioning
confidence: 99%
“…Treatment consists mainly in the avoidance of the causative allergens. Allergens implicated include phosphorus, N-Isopropyl-N-phenyl-4-phenylenediamine, ethylenediamine, dihydrochloride, cobalt naphthenate, nickel sulphate, paraphenylenediamine, gold sodium thiosulfate, zinc, squaric acid dibutylester, methylchloroisothiazolinone (26). Millican et al reported a first case of CLH after sensitization with squaric acid dibutylester (46)(47)(48).…”
Section: Treatment According To Cutaneous Pseudolymphoma Aetiologymentioning
confidence: 99%
“…Spontaneous regression is the most common course of cutaneous lymphoid hyperplasia, but lesions can also remain chronic or recur locally 2,4 . Rare examples of progression to cutaneous lymphoma have been reported, but it remains unclear whether these cases represent actual transformation of a benign lesion or rather an initial misdiagnosis of a malignant lesion 4,6,7 . Although cutaneous lymphoid hyperplasia lesions are often left untreated, possible interventions include antigen removal, excision, topical or injected corticosteroids, local radiation, laser ablation, interferon alpha, and thalidomide 2,4,8 …”
Section: Discussionmentioning
confidence: 99%